Safety and Activity of Mirvetuximab Soravtansine (IMGN853), a Folate Receptor Alpha-Targeting Antibody-Drug Conjugate, in Platinum-Resistant Ovarian, Fallopian Tube, or Primary Peritoneal Cancer: A Phase I Expansion Study - Moore, Kathleen N; Martin, Lainie P; O'Malley, David M; Matulonis, Ursula A; Konner, Jason A; Perez, Raymond P; Bauer, Todd M; Ruiz-Soto, Rodrigo; Birrer, Michael J (Journal of clinical oncology, 2017)
Purpose This phase I expansion cohort study evaluated the safety and clinical activity of mirvetuximab soravtansine (IMGN853), an antibody-drug conjugate consisting of a humanized anti-folate receptor alpha (FRα) monoclonal antibody linked to the tubulin-disrupting maytansinoid DM4, in a population of patients with FRα-positive and platinum-resistant ovarian cancer. Patients and Methods Patients with platinum-resistant epithelial ovarian, fallopian tube, or primary peritoneal cancer received IMGN853 at 6.0 mg/kg (adjusted ideal body weight) once every 3 weeks. Eligibility included a minimum requirement of FRα positivity by immunohistochemistry (≥ 25% of tumor cells with at least 2+ staining intensity). Adverse events, tumor response (via Response Evaluation Criteria in Solid Tumors [RECIST] version 1.1), and progression-free survival (PFS) were determined. Results Forty-six patients were enrolled. Adverse events were generally mild (≤ grade 2), with diarrhea (44%), blurred vision (41%), nausea (37%), and fatigue (30%) being the most commonly observed treatment-related toxicities. Grade 3 fatigue and hypotension were reported in two patients each (4%). For all evaluable patients, the confirmed objective response rate was 26%, including one complete and 11 partial responses, and the median PFS was 4.8 months. The median duration of response was 19.1 weeks. Notably, in the subset of patients who had received three or fewer prior lines of therapy (n = 23), an objective response rate of 39%, PFS of 6.7 months, and duration of response of 19.6 weeks were observed. Conclusion IMGN853 exhibited a manageable safety profile and was active in platinum-resistant ovarian cancer, with the strongest signals of efficacy observed in less heavily pretreated individuals. On the basis of these findings, the dose, schedule, and target population were identified for a phase III trial of IMGN853 monotherapy in patients with platinum-resistant disease.